State, tourism, and COVID-19 in Argentina: Implications of policies implemented in the pandemic - Schenkel, Erica (2024)
COVID-19 led to a reformulation of policies in the tourism sector, as the fall in international flows led to a renewed focus on domestic tourism. Argentina is an example of this phenomenon. During the pandemic, it promoted a local tourism agenda that had not been seen for decades. Foreign promotion and inbound (international) tourism, which used to play a leading role in the sector’s agenda, gave way to the strengthening of domestic tourism. This article analyzes the reformulation of the Argentine tourism agenda during the pandemic and its socio-territorial implications. For this purpose, we use policy analysis as a theoretical-methodological approach, particularly evaluation studies based on quantitative-qualitative methods. The three policies implemented (assistance to the national tourism sector, coordination and adaptation to the new normality, and stimulus to demand) are described and then linked to a context characterized by the lifting of restrictions and the progress of the vaccination process, features that drove tourism recovery rates from the second half of 2021. It is shown that, although in this reactivation there is evidence of a revival of domestic tourism, international tourism remains well below pre-pandemic levels. The text concludes with a series of reflections on the impact of the policies implemented in Argentina.